Analisis Promosi Dan Manajemen Resiko Pada Bmt Al Ishlah Untuk Meningkatkan Kepercayaan Masyarakat Di Kota Jambi - Ary Dean Amri; Qorry Ambiya; Ita Fitriana; Eka Rizki; Rizky Anggreyni; Syarifah Rizki Amanda (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This research aims to analyze whether the promotion and risk management at BMT Al-Ishlah affects the confidence of people in the city of Jambi. As the population of this research is the people of Jambi City. The number of research samples used is 397 respondents. The research approach uses a quantitative approach, while the research method is observation, interviews, literature studies, and questionnaires. Data analysis using parametric statistics. The result is that promotion influences increasing public trust and risk management influential in increasing public confidence. The promotion has an influence but is not significant on the trust of the people of Jambi City in using BMT Al-Ishlah products, and risk management also has an influence but is not significant in increasing the trust of the people of Jambi City in using BMT Al-Ishlah products.